Persepsi tubuh dan gangguan makan pada remaja - Mohamad Yulianto Kurniawan; Dodik Briawan; Rezzy Eko Caraka (Jurnal Gizi Klinik Indonesia, 2015)
Background: There can no longer be any doubt that adolescents do indeed have body esteem problems. Several types of research seem to suggest that this wrong behavior caused by some negative perceptions as a result of dissatisfaction with the body and a person’s level of self-confidence. Therefore they often do misperceptions of his/her body that can lead to wrong dietary behavior. It’s related to the development of more severe body image and eating-related problems.Objective: This study determined the relationship of body image perception and eating disorders in adolescents.Method: A cross-sectional study was applied in this study. The subjects were 120 new students majoring in a nutritional program in Bogor Agricultural University (IPB). They completed a questionnaire measuring appearance evaluation, appearance orientation, body areas satisfaction, overweight preoccupation, self-classified weight and eating disorders. Multidimensional Body Self-Relations Questionnaire-Appearance Scale (MBSRQ-AS) method is used to assess body image perception and Eating Attitude Test 40 (EAT-40) to predict eating disorders.Results: Descriptive analysis showed nutritional status were categorized as normal (83.3%), overweight (10.0%), obesity (4.2%) and thin (2.5%). With MBSRQ-AS method, most of the adolescents have appearance evaluation (80.0%), appearance orientation (99.2%), body areas satisfaction (80.8%), self-classified weight (71.7%) were categorized as negative, whereas overweight preoccupation (57.5%) were categorized as positive. There was (7.8%) female subject with eating disorders with more risk or have attitude the desire to eat continuously and can’t stop eating (2-3 times a month).Conclusion: Statistically using a significance level (α=5%) obtained a significant correlation between body image perception in overweight preoccupation subscale with eating disorders. However, there were no significant correlations for other subscales.